2020
DOI: 10.1007/s40201-020-00543-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hospital indoor air quality for the presence of SARS-Cov-2

Abstract: Purpose Unidentified dynamics for the causative agent of COVID-19, SARS-Cov-2, led to the critical public health issue. Suspicion for the airborne potential of SARS-Cov-2 is an important problem for its transmission and relevant epidemics. This research investigated hospital indoor air quality to SARS-Cov-2 occurrence and determination its air born potential. Methods The site study was a referral hospital with 630 beds for admitting of COVID-19 patients. Air sampling was done (n = 31) on selected wards includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 15 publications
1
44
1
1
Order By: Relevance
“…Finally, fourteen studies were eligible and included in this SR based on the inclusion/exclusion criteria, as illustrated in Fig. 1 ( WANG and YONEDA, 2020 , BUONANNO et al, 2020 , VUORINEN et al, 2020 , STADNYTSKYI et al, 2020 , CHIA et al, 2020 , FARIDI et al, 2020 , KENARKOOHI et al, 2020 , SANTARPIA et al, 2020a , SANTARPIA et al, 2020b , LIU et al, 2020 , Orenes-Piñero et al, 2020 , KIM et al, 2020 , MASOUMBEIGI et al, 2020 , RAZZINI et al (2020) ) .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, fourteen studies were eligible and included in this SR based on the inclusion/exclusion criteria, as illustrated in Fig. 1 ( WANG and YONEDA, 2020 , BUONANNO et al, 2020 , VUORINEN et al, 2020 , STADNYTSKYI et al, 2020 , CHIA et al, 2020 , FARIDI et al, 2020 , KENARKOOHI et al, 2020 , SANTARPIA et al, 2020a , SANTARPIA et al, 2020b , LIU et al, 2020 , Orenes-Piñero et al, 2020 , KIM et al, 2020 , MASOUMBEIGI et al, 2020 , RAZZINI et al (2020) ) .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the main findings of the included reviewed studies. Among the selected and included studies, eleven studies conducted experimental studies to determine the possible airborne transmission of SARS-CoV-2 in indoor air environments ( SANTARPIA et al, 2020a , SANTARPIA et al, 2020b , LIU et al, 2020 , Orenes-Piñero et al, 2020 , STADNYTSKYI et al, 2020 , FARIDI et al, 2020 , KENARKOOHI et al, 2020 , CHIA et al, 2020 , KIM et al, 2020 , MASOUMBEIGI et al, 2020 , RAZZINI et al, 2020 ). These studies were conducted in Iran (n = 3), USA (n = 2), China (n = 1), Spain (n = 1), Singapore (n = 1), Philadelphia (n = 1), Korea (n = 1) and Italy (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, preventing the airborne transmission of viruses in hospitals is a necessity based on national and international evidence [1]. By identifying the dynamics of the causative agent of SARS-CoV-2, Masoumbeigi et al [2] showed the significance of the airborne infection potential of the related epidemics. Their results indicated the importance of the hospital's indoor air quality monitoring system.…”
Section: Introductionmentioning
confidence: 99%